Prevalence of scoliosis and congenital heart disease based on school screening in Jinghong City, Yunnan Province - Qian, Genghao; Zhang, Li; Zhao, Zhi; Wang, Yingsong; Lu, Jiang; Bi, Ni; Yang, Xiaochen; Xie, Weijie; Shi, Zhiyue; Li, Tao; Zhang, Zhaoquan; Song, Zhibo (Frontiers in Public Health, 2025)
ObjectiveTo investigate the prevalence of scoliosis and congenital heart disease (CHD) in the same area and to explore the relationship between them according to a joint school screening.MethodsAll students aged 6–15 years in 20 schools in Jinghong City, Yunnan Province, China was screened for scoliosis and CHD. Scoliosis screening completed through the Adam's forward bending test with scoliometer measurement, and CHD screening completed through auscultation combined with portable echocardiography (ECHO). The gender, age, distribution of ethnic groups, types of CHD, angle of trunk rotation (ATR) and location of scoliosis were recorded. The severity was divided into 3 grades by ATR. Then the relationship between scoliosis and CHD was analyzed.ResultsA total of 17,134 students was screened with a prevalence of suspected scoliosis of 1.7% (298 students), and the prevalence of suspected scoliosis in female was higher than that in male (2.4 vs. 1.2%, P < 0.001), which increased with age (P < 0.01). The prevalence of suspected scoliosis was no different among ethnic groups (P > 0.05). The severity of scoliosis was mainly grade 1 (68.5%), followed by grade 2 (27.2%) and grade 3 (4.4%). And scoliosis was mainly located in lumbar (37.6%). The prevalence of CHD was 3.15‰, and there was no difference in the prevalence of CHD between different gender, age and ethnic groups (P > 0.05). The most common type of CHD was atrial septal defect (27.78%), followed by ventricular septal defect (16.67%). There was only one CHD student in 298 suspected scoliosis students.ConclusionThe prevalence of suspected scoliosis among primary school students was 1.74%, while the prevalence of congenital heart disease was 3.15‰ in Jinghong City, Yunnan Province. And the incidence of CHD in patients with mild suspected scoliosis was low and close to that in normal population.